3D Cancer Models: The Need for a Complex Stroma, Compartmentalization and Stiffness - Pape, Judith; Emberton, Mark; Cheema, Umber (Frontiers in Bioengineering and Biotechnology, 2021)
The use of tissue-engineered 3D models of cancer has grown in popularity with recent advances in the field of cancer research. 3D models are inherently more biomimetic compared to 2D monolayers of cells cultured on tissue-culture plastic. Nevertheless 3D models still lack the cellular and matrix complexity of inherent tissues. This review explores the different 3D models currently used, outlining their benefits and limitation. Specifically, this review focuses on stiffness and collagen density, compartmentalization, tumor stroma cell population and extracellular matrix composition. Furthermore, this review explores the methods utilized in different models to directly measure cancer invasion and growth. Of the models evaluated, with PDX and in vivo as a relative “gold standard”, tumoroids were deemed as comparable 3D cancer models with a high degree of biomimicry, in terms of stiffness, collagen density and the ability to compartmentalize the tumor and stroma. Future 3D models for different cancer types are proposed in order to improve the biomimicry of cancer models used for studying disease progression.